The promotion of social sustainability by micro-level social inclusion in a multicultural context: literature review and interview evidence - Fan, Qianqian (Frontiers in Sociology, 2025)
Drawing on multicultural theory, social capital theory, and sustainability theory, this paper explores social sustainability in a multicultural context. A two-stage research design was employed, consisting of a systematic literature review and interview-based text analysis. In the first stage, 210 papers were systematically reviewed. By extracting conceptual elements, new constructs of micro-level social inclusion, individual social capital, and individual social sustainability were defined. A preliminary social sustainability model—encompassing social inclusion, social capital, and social sustainability—was proposed. Relationship-focused research addressed gaps in existing literature, revealing interactions among these constructs and spurring refinements to the preliminary model. In the second stage, 130 short interview videos (totaling 173 participants) were analyzed. Empirical evidence from these interviews confirms that micro-level social inclusion and individual social capital positively affect social sustainability. The results of this paper are derived from a systematic study of the literature, and the results are verified by the conclusion of interview text analysis. This paper presents an innovative viewpoint by foregrounding micro-level social inclusion and individual social capital in daily life as drivers of social sustainability. Findings demonstrate that micro-level social inclusion fosters individual social capital, which, in turn, is a potent force behind social sustainability. The study thus offers a new research agenda, expands the field of individual social capital research, and provides practical and policy insights for further research and implementation.